Angular Relationship between Frankfort Horizontal Plane and Sella-Nasion Plane in Nepalese Orthodontic Patients: A Cephalometric Study - Giri, Jamal; Pokharel, Prabhat Ranjan; Gyawali, Rajesh (Orthodontic Journal of Nepal, 2017)
Introduction: The angle between Frankfort horizontal (FH) plane and Sella-Nasion (SN) plane is considered to be 7°. Various studies have shown that the FH-SN angulations could vary; which can affect cephalometric diagnosis. Objective: To determine average FH-SN angle for a group of Nepalese orthodontic patients. The secondary objectives were to assess whether the FH-SN angle exhibits sexual dimorphism and to evaluate the FH-SN angle in different skeletal relationships. Materials & Method: Lateral cephalograms of 238 orthodontic patients were hand traced and the angle between the FH and SN plane was measured and recorded. The cephalograms were also classified as skeletal Class I, II or III cases using Wits appraisal. Result: The average FH-SN angle was 6.71° ± 3.13°. FH-SN angle was greater in female samples compared to males. However, the difference was not statistically significant. Similarly, the ANOVA analysis revealed no significant difference between FH-SN angles in different skeletal relationships. Conclusion: The average FH-SN angle for a group of Nepalese orthodontic patients was 6.71° ± 3.13°. There was no statistically significant difference in FH-SN angle between skeletal Class I, II and III relationships